Sistem Pakar Untuk Diagnosa Hama dan Penyakit Pada Bunga Krisan Menggunakan Forward Chaining - Hanip Afandi; Danang Arbian Sulistyo (LP2M INSTITUT TEKNOLOGI DAN BISNIS ASIA MALANG, 2019)
Chrysanthemum flowers are a type of flowering plant that is often planted as an ornamental plant or cut flower. Chrysanthemum flower farmers on average have less knowledge about pests and diseases in chrysanthemum flowers that are difficult to identify, so that it is too late in handling and prevention which will result in a decrease in the yield of chrysanthemum flowers. Expert system can solve this problem by designing a web-based computer system integrated with database and programming languages such as PHP-MySQL so as to help chrysanthemum farmers in Poncokusumo to diagnose pests and diseases. Expert system applications in decision making using inference engines such as Forward Chaining that works by tracing cases based on rules on the decision tree. Diagnosis of Pests and Diseases using Forward Chaining method. In this study the types of diseases that can be diagnosed as many as 12 diseases. The results of the system implementation of the system gives questions in the form of symptoms that must be answered by the farmerbased on symptoms experienced by chrysanthemum flowers and the results of the process the system will provide information on what pests or diseases to get treatment solutions and prevention.Tests used are accuracy testing with 21 data tester.